The Power of Peers Unleashed in Motivating Elementary Learning Around the World: Kekuatan Teman Sebaya Dilepaskan dalam Memotivasi Pembelajaran SD di Seluruh Dunia - Fitri, Nadiya; Astuti, Ruli (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of peers and their impact on the learning motivation of fifth-grade students at Sidokare 1 Public Elementary School. Utilizing a descriptive qualitative approach, data was collected through interviews and documentation from both students and teachers. Findings indicate that peers significantly contribute to motivating learning by providing encouragement, studying together, and acting as problem-solving companions. The positive impact of peers on learning motivation underscores their importance as benchmarks and motivators for academic achievement. Understanding peer dynamics in elementary education is crucial for fostering supportive learning environments and enhancing student engagement. Further research focusing on peer influence among adolescents can provide additional insights into developmental aspects of peer interactions and their effects on learning motivation.Highlight: Peer Encouragement: Crucial for motivating learning and academic achievement. Enhancing Student Engagement: Understanding peer dynamics fosters supportive learning environments. Research Method Importance: Descriptive qualitative approach explores peer interactions' impact effectively. Keyword: Peer influence, Learning motivation, Elementary education, Descriptive qualitative research, Academic achievement.